Viability of university service learning to support movement integration in elementary classrooms: Perspectives of teachers, university students, and course instructors. (May 2018) - Michael, Robert D.; Webster, Collin A.; Egan, Cate A.; Stewart, Gregory; Nilges, Lynda; Brian, Ali; Johnson, Robert; Carson, Russell; Orendorff, Karie; Vazou, Spyridoula
Abstract: This study examined the views of elementary classroom teachers (CTs), preservice CTs (PCTs), and course instructors who were involved with a university course that drew upon principles of constructivism and SL to prepare preservice CTs to use MI. Focus groups were thematically analyzed using constant comparison techniques to identify perceived successes and challenges of the course. Findings centered on three major themes, including real-world context, learning embedded in a social context, and scaffolding. This study adds to the emerging research base on school-university partnerships to support both preservice and inservice educational initiatives to generate and sustain physically active school communities. Highlights: Three themes emerged real-world context, learning embedded in a social context, and scaffolding. Classroom-based SL experiences can facilitate learning to integrate movement. Classroom-based SL experiences can provide positive experiences for all stakeholders. Mutual benefits is an important element of instructional design.